Substitution in the South African context - constitutional principles in action - Pinto, Tayla (Department of Public Law, 2024)
This thesis is a cumulative analysis of the role of substitution as a remedy for maladministration in the public procurement context within the modern constitutionalism in South Africa. It considers the role and position of substitution from a technical and theoretical point of view. The cumulative analysis is aimed at illustrating that substitution plays an important role within the judicial review remedial framework, that the courts have applied their minds and developed a robust test for substitution and that this is an important tool and process for the ascertainment of the ideals of the democratic and constitutional project outline in the Final Constitution (Constitution). This analysis is conducted against the backdrop of public procurement and its links to service delivery and the furtherance of the democratic project. Substitution to this end can be seen as an example of the constitutional principles envisaged by the Constitution in action in that it promotes the rule of law while protecting and promoting human rights.